Cognitive functioning and associated factors in older adults in South Africa - K Peltzer; N Phaswana-Mafuya (South African Journal of Psychiatry, 2012)
Objective. To investigate cognitive functioning and associated factors in a national probability sample of older South Africans who participated in the Study of Global AGEing and Adult Health (SAGE) in 2008.